5-Aminosalicylic acid inhibits the impaired epithelial barrier function induced by gamma interferon. (January 1996) - Di Paolo, M C; Merrett, M N; Crotty, B; Jewell, D P
Abstract : Gamma interferon (IFN gamma) impairs epithelial barrier function and induces HLA-DR expression on colonic cancer cell lines. Salicylates have been shown to reduce IFN gamma induced HLA-DR expression. The effect of 5-aminosalicylic acid (5-ASA) on IFN gamma induced changes in transepithelial resistance and permeability was investigated in HT29 clone 19A and Caco 2 monolayers. Monolayers were incubated with different concentrations of IFN gamma (100, 500, 1000, and 3000 U/ml) and 5-ASA. IFN gamma induced class II expression in a time and dose dependent manner in HT29:19A but not Caco 2 cells. HT29:19A monolayers incubated with both IFN gamma and 5-ASA showed lower HLA-DR expression compared with monolayers incubated with IFN gamma alone. Electrical resistance and 14C-mannitol flux across HT29:19A monolayers were significantly changed by IFN gamma. Addition of both IFN gamma and 5-ASA to the basolateral surface of the monolayers significantly reduced paracellular permeability compared with addition of IFN gamma alone. These data show that IFN gamma is able to induce HLA-DR expression and to impair the barrier function of HT29:19A monolayers, and that 5-ASA reduces IFN gamma induced HLA-DR expression and inhibits the effects of IFN gamma on epithelial barrier function.